NORMATIVE-LEGAL REGULATION OF UNLIMITED TILLAGE OF FORESTS - Khomyachenko, Svitlana I.; Khotsianovska, Natalya F.; Chasova, Tatiana O. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the purpose of the scientific article is to study and analyze theoretical approaches to defining the concept and content of the definition of "illegal felling of the forest" as well as the study of the legal regulation of illegal logging, namely the provisions of civil, administrative and criminal liability. Methods: the Improvement of the legislative framework, which provides legal responsibility for the illegal cutting out of the forest. Results: environmental offenses are offenses that require priority consideration and bring the perpetrators to justice. Illegal felling of the forest is one of the varieties of environmental offenses, which involves civil, administrative and criminal responsibility for the commission of unlawful acts. The current state of logging is worrying, therefore, inspections are carried out by the competent authorities, criminal proceedings are opened, civil claims are filed and administrative protocols are drawn up, which is a rather positive trend. Discussion: the need for a clear legal separation of administrative and criminal responsibility for the illegal logging.